Implementasi Integrasi Ilmu Agama, Sains dan Teknologi di Madrasah Aliyah Unggulan Darul ‘Ulum Step-2 IDB KEMENAG RI Rejoso Peterongan - Agus Moh. Sholahuddin (EDUKASIA: Jurnal Pendidikan dan Pembelajaran, 2022)
Many students are more dominant in understanding and studying religious sciences. They are less able to master Science and Technology, in this global era, students should also be able to master Science and technology. The Superior MA Darul 'Ulum uses an integrated curriculum, namely the Integration of Religion, Science, and Technology. The institution tries to provide knowledge to its students so that they can compete and be able to answer the challenges of the times in this global era, especially in science and technology. This research focuses on how to plan the implementation of the integration of religion, science, and technology, how to implement the integration of religion, science, and technology, how to evaluate the implementation of the integration of religion, science, and technology, and how the results of the implementation of the integration of religion, science, and technology in the Superior MA Darul 'Ulum. The objectives are to find out the planning of the Implementation of the Integration of Religion, Science, and Technology, to know the Implementation of the Integration of Religion, Science, and Technology, to know the evaluation of the Implementation of the Integration of Religion, Science and Technology, and to know the results of the Implementation of the Integration of Religion, Science and Technology in Superior MA Darul 'Ulum. This research was conducted at MAU-DU Jombang with the methods used were interviews, observation, and documentation. The data analysis used included: data reduction, data presentation, and drawing conclusions in the learning process of integrating religion and science. Integrated learning requires planning in the form of lesson plans developed according to the competencies possessed by the teacher. The integrated material is science related to the verses of the Qur'an. The methods used in the learning are discussions, observations, lectures, experiments, field trips, questions and answers, and assignments. The media used are print and electronic media, both traditional and modern. Among them are printed books, whiteboards, laboratories, computers, LCDs, TVs, tapes, recorders, replicas, and the real world. The learning evaluation used has two components, namely to assess student learning outcomes, an evaluation is carried out which includes: Daily Assessment, Mid-Semester Assessment, Final Semester Assessment, Practice Exams, Final Projects, and evaluation of student records. The results obtained by students are understanding knowledge as a whole, students gaining knowledge that they have dug for themselves and are able to look at it from various disciplines and from various points of view and can compete for achievements at the olympiads that have been held related to science, Islam and technology.